Theoretical computer science - Preparata, F. (Franco P.) (C.I.M.E. summer schools, 2011)
R.E. Miller: Parallel program schemata.- D.E. Muller: Theory of automata.- R. Karp: Computational complexity of combinatorial and graph-theoretic problems.